(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This paper analyzes the agreement of non-prosecution, conceived by the National Council of Prosecution Service, in article 18 of Resolution nº 181/2017. The study shows that this new consensus instrument, introduced in the sphere of Brazilian criminal, suffers from formal and material unconstitutionalities, which must be recognized by the Judiciary.